A 0.18um CMOS Low Noise Amplifier for 3-5ghz UWB Receivers - Malika Begum, N; Yasmeen, W (International Journal of Engineering and Technology, 2018)
This paper presents an Ultra-Wideband (UWB) 3-5 GHz Low Noise Amplifier (LNA) employing Chebyshev filter. The LNA has been designed using Cadence 0.18um CMOS technology. Proposed LNA achieves a minimum noise figure of 2.2dB, power gain of 9dB.The power consumption is 6.3mW from 1.8V power supply.Â Â